ANALYSIS OF THE MAIN DUTIES & FUNCTIONS OF THE NATIONAL ZAKAT COMMUNITY AGENCY OF MOJOKERTO CITY BASED ON POAC'S PERSPECTIVE - Aulia Jasmine Zalfania Azzahra; Sarah Nurlaily; Kezhia Febrin Nadia Krista; Nadila Rizki Auliya; Meirinawati; Trenda Aktiva Oktariyanda (Jurnal Penelitian Progresif, 2026)
This study aims to analyze the management of zakat management at BAZNAS Mojokerto City using the POAC (Planning, Organizing, Actuating, Controlling) approach . This study uses a descriptive qualitative method with data collection techniques through literature studies , documentation , and analysis of institutional reports . The results of the study indicate that BAZNAS Mojokerto City has implemented management functions quite optimally , especially in the aspect of zakat potential- based planning and the implementation of innovative service-based programs. However, several obstacles are still found such as less than optimal organizational coordination , less than optimal data integration , and a monitoring system that is still output - oriented and not fully impact - oriented . The implications of this study show the importance of strengthening outcome- based monitoring and evaluation systems and data integration to improve the effectiveness of zakat management within a public management framework .